STEPS-T Program Improves Endovascular Treatment Outcomes of Acute Ischemic Stroke; A 6-Year Study - Hassan, Ameer E.; Rabah, Rani R.; Preston, Laurie; Tekle, Wondwossen G. (Frontiers in Neurology, 2020)
Background: Early endovascular recanalization of occluded vessels in acute ischemic stroke (AIS) is a major contributor to good clinical outcome. We report the analysis of all AIS patients throughout a 6-year experience following the deployment of a quality initiative aiming at improving care, speed and maintaining quality for AIS treatment. Methods: Using a prospectively collected endovascular database at a comprehensive stroke center between 2012-17, workflow/outcomes were recorded. There were no exclusion criteria. During the first year, a quality program employing “digital-object” technology, staff education, and workflow improvement was implemented to reduce time-to-treatment. Using electronic recording, workflow times were collected for onset (TO), CT (TCT), door (TD), angiography-suite (TA), groin puncture (TG), DSA (TDSA), micro-catheter placement (TM), and recanalization (TR). Recanalization time (TG-TR) and workflow intervals were compared at Year 1 and 6. Results: Analysis of 382 patients (aged 71.3±12,9) undergoing mechanical thrombectomy for AIS (206 male and 176 female) was performed. Recanalization time was significantly reduced from 82 min in 2012 to 34 min by 2017 (IQR 52- 117 min and 23-49 min), a 59% reduction (P < 0.001). Further, consistent year-over-year reductions in setup time (TA-TG) (44% improvement) and TCT to TA times were observed. During the same period, clinical outcome significantly improved year-over-year as measured with the modified Rankin Scale 0-2 (33%, 37%, 38%, 41%, 53%, and 58%). Conclusions: Significant improvements were observed following the deployment of a quality initiative enabling iterative evidence-based process improvements, thereby sustaining significant reductions in time-to-treat and improved clinical outcomes for AIS patients.